Analisis Pemetaan Masalah Guru dan Siswa Pada Pembelajaran IPA SD: Analisis Pemetaan Masalah Guru Dan Siswa Pada Pembelajaran IPA SD - Merry Berlian; Fatimah Azzahra; Rian Vebrianto (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to conduct a comprehensive mapping of various obstacles encountered by teachers and students in the Science learning process at the Elementary School level. The phenomenon of low scientific literacy and the predominance of conventional methods serve as the primary background for this analysis. The research method employed is qualitative descriptive, utilizing a root cause analysis technique through the Fishbone Diagram (Ishikawa). The mapping results indicate that the problems in Science education are categorized into four primary dimensions. First, in the human dimension (Man), it was found that there is a low mastery of Pedagogical Content Knowledge (PCK) among teachers and a high prevalence of student misconceptions. Second, in the method dimension (Method), learning remains teacher-centered with minimal inquiry-based activities. Third, in the material dimension (Material), the limited availability of teaching aids and insufficient technology integration act as major barriers to manifesting abstract concepts. Fourth, in the environment dimension (Milieu), the lack of a supportive school ecosystem for an experimental culture exacerbates the quality of learning outcomes.This study concludes that this problem mapping can serve as a foundation for schools to develop integrated improvement strategies, through both teacher pedagogical training and the procurement of environment-based learning media